Ilman wa Rūhan’ Approach in Al-Qur’an Learning to Develop Qur’anic Personality at Al-Fahmi Integrated Islamic Junior High School, Palu City - Ria Indriani; Kamaruddin Kamaruddin (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2026)
This study examines the implementation of the “ilman wa rūḥan” approach in Qur’anic learning to develop Qur’anic personality among students at SMP IT Al-Fahmi Palu. Using a qualitative case study design, the research explores the integration of intellectual (ilman) and spiritual (rūhan) dimensions in the learning process. Data were collected through observation, interviews, and documentation. The findings reveal that the approach is implemented through structured Qur’anic programs, including tahfidz, muraja’ah, tadabbur, congregational prayers, and character-building activities integrated into daily school culture. The approach contributes positively to the development of students’ Qur’anic personality, reflected in discipline, honesty, responsibility, politeness, and spiritual awareness. Supporting factors include teacher commitment, parental involvement, and an Islamic school environment, while challenges involve differences in students’ abilities and limited learning time. This study highlights that the “ilman wa rūḥan” approach provides a holistic model for Qur’anic education that integrates cognitive, affective, and spiritual development.